Legal Issues Regarding Interfaith Marriage According to Indonesian Marriage Laws: Problematika Hukum Terhadap Perkawinan Beda Agama Menurut Undang Undang Perkawinan - Sagala, Ermiyani; Fibrianti, Nurul (Annual Review of Legal Studies, 2024)
This research aims to examine the legal study on the legalization of interfaith marriage and how the government regulates interfaith marriage. This research utilizes a normative legal research method, specifically scientific research, to gather facts that align with legal arguments from a normative perspective, which inventories literature research or studies legal documents from a doctrinal standpoint. Data collection techniques involve documentary research supported by field research to obtain basic legal documents (legal approach) and facts (factual approach) to identify primary, secondary, and tertiary legal documents using a legal concept approach. Thus, from this research, it can be concluded that judges recognize interfaith marriage because of the social and legal aspects they consider. Therefore, this research can discuss both social and legal aspects. The mechanism for applying for interfaith marriage is through court determination according to the provisions of Law Number 23 of 2006 concerning Population Administration. According to Article 35, the registration of marriage with individuals of different faiths must be done upon the court's order. The application is made through the mechanism of a district court decision. Couples marrying from different faiths abroad must go through this process as there are no regulations regarding interfaith marriage in Indonesia. Therefore, the registration of interfaith marriage must be done through a court order. The marriage certificate can be obtained at the Civil Registry Office.